Parvovirus B19-induced aplastic crisis in a kidney transplant recipient - Strakosha, Ariana; Rista, Elvana; Imeraj, Amantia; Pasko, Nevi; Cadri, Vilma; Dedej, Teuta (The Journal of Infection in Developing Countries, 2026)
Introduction: Parvovirus B19 infection is a rare, but important cause of severe anemia in kidney transplant recipients. Case presentation: We present the case of a 32-year-old male with end-stage kidney disease undergoing living-donor kidney transplantation and subsequently developing profound anemia. Our case emphasizes the heightened risks of developing infectious complications among kidney transplant recipients due to their intense immunosuppressed state and the diagnostic challenges parvovirus B19 presents in this population. In this context, maintaining a high index of clinical suspicion in recipients presenting with severe, erythropoietin-resistant anemia and reticulocytopenia is essential in ensuring a timely diagnosis. Conclusions: Adopting a tailored, multidisciplinary approach that balances the risks of acute rejection with the need to reduce immunosuppression to promote viral clearance, is paramount to improving hematological and allograft outcomes.